Pengaruh Pola Asuh Orang Tua Terhadap Dekadensi Moral Siswa Sekolah Dasar - Sintya Siahaya; Abigael An Tiblola; Samel Sopakua (Syntax Idea)
Moral and character education is an important aspect of individual development, especially at the primary education level, one of the factors that play a role in the formation of student morals is parenting. The purpose of this study is to investigate the effect of parenting on the moral decadence of elementary school students. This study used quantitative research methods. Data collection techniques were carried out by surveys distributed to parents of students of SDN 1 Hative Kecil Ambon. The sampling technique was carried out using random sampling technique. The data that has been collected is then analyzed using simple linear regression analysis using the help of the SPSS program. The results showed that parenting patterns affect the moral decadence of elementary school students. Authoritarian and permissive parenting have a positive relationship with moral decadence, while democratic parenting has a negative relationship with moral decadence. So it can be concluded that parents are influential in the development of children's character.